Group Visits for Overdose Education and Naloxone Distribution in Primary Care: A Pilot Quality Improvement Initiative. Issue 12 (16th October 2017) - Spelman, Juliette F; Peglow, Stephanie; Schwartz, Amy R; Burgo-Black, Lucille; McNamara, Katelyn; Becker, William C
Abstract: Objective: Opioid prescribing for chronic pain significantly contributes to opioid overdose deaths in the United States. Naloxone as a take-home antidote to opioid overdose is underutilized and has not been evaluated in the high-risk chronic pain population. The objective was to increase overdose education and naloxone distribution (OEND) to high-risk patients on long-term opioid therapy for pain by utilizing group visits in primary care. Design: Quality improvement intervention among two primary care clinics. Setting: A large, academic facility within the Veterans Health Administration. Subjects: Patients prescribed ≥100 mg morphine-equivalent daily dose or coprescribed opioids and benzodiazepines. Methods: One clinic provided usual care with respect to OEND; another clinic encouraged attendance at an OEND group visit to all of its high-risk patients. Results: We used attendance at group visits, prescriptions of naloxone issued, and patient satisfaction scores to evaluate this format of OEND. Key Results: Group OEND visits resulted in significantly more naloxone prescriptions than usual care. At these group visits, patients were engaged, valued the experience, and all requested a prescription for the naloxone kit. Conclusion: This quality improvement pilot study suggests that OEND group visits are a promising model of care.